Meningkatkan Keterampilan Desain Logo Produk Menggunakan Aplikasi Desain Grafis Berbasis Artificial Intelligence untuk Pelaku UMKM - Hanna Aulia; Muh Mirwan Hariri; Achmad Midanul Arifin; Shofia Rahmadani (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Surviving and running a business in the era of Industry 4.0, which emphasizes the widespread transformation of digital technology use, is certainly a challenge for MSME players. The purpose of this study is to provide teaching intervention in graphic design for MSME product packaging and logos using AI-based applications. This study uses a mixed-methods design with a structured intervention over eight weeks involving 20 MSME participants. The stages of this study include (a) initial assessment and participant selection, (b) intervention procedures, (c) post-intervention assessment, and (d) data evaluation and analysis. The results show that this framework is effective; all participants successfully exceeded the competency threshold (70%) and showed a significant increase in design creativity. Thus, it is concluded that the integration of AI through structured teaching is an evidence-based strategy for accelerating MSME digital design literacy, providing important implications for empowerment programs and digital economic transformation.